Browsing Documents on a Dense Embedding that Captures Theme Evolution - Perina, Alessandro; Jojic, Nebojsa (2012)
We describe a new interaction strategy for browsing documents consisting of text and images. The browser represents a collection of documents as a grid of key words with varying font sizes that indicate the words' weights. The grid is computed using the counting grid model so that each document approximately matches in its word usage the word weight distribution in some window in the grid.
Under Submission